EDUKASI DAN DEMONSTRASI SENAM NIFAS PADA IBU PASCA PERSALINAN - Mawarti, Indah; Yusnilawati, Yusnilawati; Sari, Putri Irwanti; Oktaria, Rina; Milawati, Birgitta Arta; Halijah, Halijah (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Hospitals play a key role in promoting health through education, especially for patients and their families. One effective method to support postpartum recovery is postpartum exercise, which helps restore bodily functions, promote uterine involution, and prevent complications. At the Mina Inpatient Ward of RSI Arafah Jambi, many postpartum mothers had not received proper education about these exercises. To address this, a community service activity was held from April 29 to May 12, 2025, targeting 16 postpartum mothers. Five mothers received only verbal education due to limited mobility, while 11 joined both education and exercise demonstrations. Observations and discussions showed improved knowledge and skills, with most mothers able to recall and correctly perform the exercises. Their active participation and positive feedback highlighted the effectiveness of the educational approach. This initiative proves valuable in enhancing postpartum recovery and is recommended for continued integration into hospital health promotion programs.